Studi Komparasi Hasil Pemijahan Induk Ikan Mas (Cyprinus carpio) Menggunakan Metode Alami, Semi Buatan dan Buatan - Ardana Kurniaji; Ihwan Ihwan; Diana Putri Renitasari; Siti Aisyah Saridu; Zainal Usman; Syafitrah Rahman (Intek Akuakultur, 2022)
Common carp (Cyprinus carpio) has become the option of aquaculture commodities which are generally found in farmers. This study aimed to evaluate the comparison of different breeding methods between natural, semi-artificial and artificial to the production of seed. The research methods included water and tank preparation, broodstock management, breeding activity, hatching eggs, rearing 7 days of larvae, nursery up to 30 days and harvesting. The results showed that there was a decrease in the weight of female fish after breeding with a percentage of 11,27% naturally, 6,11% semi artificially, and 5,7% artificially. The fecundity of the broodstock produced differed between treatments, namely by natural spawning 128,000 eggs, semi-artificial 68,034 eggs and artificially 24,537 eggs. Fertilization rate of fish obtained from natural breeding was 72%, semi-artificial 89% and artificial 81%. The hatching rate of fish obtained from natural breeding was 56%, semi-artificial was 79% and artificial was 63%. The survival rate of larvae was 90% from natural breeding broodstock, 75% from semi artificial breeding broodstock and 70% from artificial breeding broodstock. Seed survival rate was 15% from natural breeding broodstock, 12% from semi artificial breeding broodstock and 7% from artificial breeding broodstock. The weight absolute growth rate of seeds was 0.37 g with a length of 3.7 cm from natural breeding, 0.43 g with a length of 3.1 cm from a semi-artificial breeding and 0.25 g with a length of 2.5 cm from an artificial breeding. During the research, it was found that the water quality was still at optimal levels for common carp growth.